2021
DOI: 10.1097/md.0000000000024575
|View full text |Cite
|
Sign up to set email alerts
|

Superb microvascular imaging for detecting carpal tunnel syndrome compared with power Doppler ultrasonography

Abstract: Background: Sonography enhances diagnostic accuracy by the detection of the epineural or intraneuronal blood flow. [ 1 – 4 ] Power Doppler ultrasonography (PDUS) in carpal tunnel syndrome (CTS) has been previously studied and shown to be valid and reliable for grading the intraneural flow. [ 3 , 4 ] However, superb microva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…We also found that the blood flow signal area measured using SMI had a relatively stronger correlation with the median nerve compression ratio and neuropathy severity (measured by NCS) compared with PDUS. Overall, these findings suggest that SMI, which enables visualization of low volume and low velocity blood flow ( 18 , 19 , 29 ), is better than CDUS and PDUS for assessing median nerve pathology in CTS patients.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…We also found that the blood flow signal area measured using SMI had a relatively stronger correlation with the median nerve compression ratio and neuropathy severity (measured by NCS) compared with PDUS. Overall, these findings suggest that SMI, which enables visualization of low volume and low velocity blood flow ( 18 , 19 , 29 ), is better than CDUS and PDUS for assessing median nerve pathology in CTS patients.…”
Section: Discussionmentioning
confidence: 82%
“…Second, their data showed a ceiling effect because vascularity was classified into only 4 groups based on the number and morphology of the blood flow signal areas, with no separate classifications for blood flow signal counts ≥3. As such, the utility of SMI for assessing CTS remains controversial and further meta-analyses are required ( 19 ). Additionally, those studies only used the Aplio500 device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation